2013
DOI: 10.1242/jeb.080077
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral fins aid in navigation of a complex environment by bluegill sunfish under sensory deprivation conditions

Abstract: SUMMARYComplex structured environments offer fish advantages as places of refuge and areas of greater potential prey densities, but maneuvering through these environments is a navigational challenge. To successfully navigate complex habitats, fish must have sensory input relaying information about the proximity and size of obstacles. We investigated the role of the pectoral fins as mechanosensors in bluegill sunfish swimming through obstacle courses under different sensory deprivation and flow speed conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
3
24
0
1
Order By: Relevance
“…In contrast, proprioceptive capacity of the fins (e.g. caudal fin) may facilitate responses to flow pulses from the caudal direction that oppose ambient flow (Flammang and Lauder, 2013;Williams et al, 2013). The strength of a stimulus relative to the strength of alternative environmental cues has been shown to influence the type and number of escape responses in animals, including fish (Abrahams and Kattenfeld, 1997;Domenici, 2010a; D. G. Roche, Effects of biotic and physical stressors on fish swimming performance and behavior, PhD thesis, Australian National University, 2014).…”
Section: Peak Velocity and Accelerationmentioning
confidence: 99%
“…In contrast, proprioceptive capacity of the fins (e.g. caudal fin) may facilitate responses to flow pulses from the caudal direction that oppose ambient flow (Flammang and Lauder, 2013;Williams et al, 2013). The strength of a stimulus relative to the strength of alternative environmental cues has been shown to influence the type and number of escape responses in animals, including fish (Abrahams and Kattenfeld, 1997;Domenici, 2010a; D. G. Roche, Effects of biotic and physical stressors on fish swimming performance and behavior, PhD thesis, Australian National University, 2014).…”
Section: Peak Velocity and Accelerationmentioning
confidence: 99%
“…The fin rays of bluegill sunfish (Lepomis macrochirus), a model species for the study of fin-based propulsion, respond to fin ray deflections and have putative mechanoreceptor structures associated with nerves that run along the fin rays from base to distal tip [4]. The ability of L. macrochirus to interpret the movement and position of their fins, a form of mechanosensation distinct from the sensation of surface touch, is important for navigating complex environments [5] and modulating rhythmic fin movements [6]. While a key feature of the tetrapod somatosensory system is the tactile perception of object movement over the skin, it is unknown whether membranous fins may function as passive touch sensors in the absence of extensive fin movement.…”
Section: Introductionmentioning
confidence: 99%
“…As many recent studies have reported that fish can actively deform their fins to achieve different types of locomotion, more and more researchers have realized the importance of these flexible propulsion surfaces on enchancing ability of swimming. Such propulsion surfaces include dorsal fins [2][3][4] and pectoral fins [5][6][7] in body and caudal fin (BCF) propulsion and ribbon fins [8][9][10] in median and paired fin (MPF) propulsion. As the most conspicuous appendage of the fish's body, the caudal fin has also been studied extensively [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%